PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI PEMBIASAAN KEGIATAN KEAGAMAAN DI SMKN 1 POGALAN - Wahyu Widyatama; Mukayat Al Amin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the formation of students' religious character and religious activities at SMK Negeri 1 Pogalan. This research employs a qualitative approach with a descriptive-analytical method. Data sources consist of both primary and secondary data. Data collection techniques were conducted through interviews, observations, and documentation. The results of this study indicate that the formation of students' religious character through the habituation of religious activities at SMK Negeri 1 Pogalan begins with classroom learning, providing material based on the curriculum, syllabus, and lesson plans (RPP), which is then implemented through routine religious practices. These religious activities include cultivating the 5S culture (Salam / Greeting, Senyum / Smiling, Sapa / Courteous Addressing, Sopan / Politeness, Santun / Manners), congregational Dhuha prayer, reciting the Al-Qur'an before starting lessons and praying at the end of lessons, congregational Zuhur prayer, Friday prayer, Friday almsgiving (Infaq), "Healthy and Clean Friday" programs, the Commemoration of Islamic Holidays (PHBI), and the Pesantren Kilat (intensive Islamic boarding school program) during Ramadan.